Menjaga Keselamatan dan Peningkatan Kesejahteraan Relawan Sampah Melalui Penerapan Nilai Budaya Betulungan - Muhammad Sultan; Ilham Abu; Sutrisno Sutrisno; Sunardi Sunardi (Badan Penelitian and Pengembangan (Balitbang), Padang, West Sumatra, Indonesia, 2023)
Safety aspect and welfare level of garbage volunteers are often neglected. This study aims to find the right strategy in maintaining the safety and improving the welfare of garbage volunteers in Samarinda City. This type of qualitative research with a phenomonological design. The informants were five garbage volunteers in Teluk Lerong Ulu Village, Samarinda City who were selected by purposive sampling with the criteria of working for at least three years, being able to communicate effectively, and being willing to be interviewed. The research was carried out in January 2023 through interviews, observation and literature studies. Data were analyzed through reduction, data presentation, and drawing conclusions. The results of the study obtained information that garbage volunteers continued to carry out their routine of transporting household waste in residential areas even though they were not workers. They work without paying attention to work safety and without a steady income. The Samarinda City Government through the Environmental Service can provide safety equipment and fittings and pay attention to the welfare of waste volunteers by providing a decent income. In addition, the cultural values of Betulungan within the Samarinda City community can be implemented to help waste volunteers stay safe and live a decent life.